Flow Experiences in Shopping Activities: Testing Materialistic Goal Orientation as an Antecedent - Amy Isham (Psychological Reports, 2025)
Given that flow experiences when shopping can encourage positive brand attitudes and purchase behaviours, consumer psychologists are interested in the antecedents to flow within retail environments. Emerging findings suggest that a materialistic goal orientation can undermine an individual’s tendency to have optimal experiences of flow. However, this existing work has been conducted largely within the field of Environmental Psychology and thus focused on flow experiences that occur in more ecologically sustainable activities. We hypothesized that materialism may not have the same flow-limiting effects when participants are engaged in shopping activities, which are more in line with the goals of highly materialistic individuals. Across two studies, we tested the relationship between materialism and the experience of flow during shopping activities using cross-sectional (N = 886) and experimental (N = 140) methods. Contrary to our hypothesis, both studies documented a negative effect of materialism on flow experiences when shopping, and this was not moderated by the type of store browsed. Accordingly, it appears that a materialistic goal orientation limits the extent to which people can have enjoyable flow experiences even during activities which are consistent with the life goals of highly materialistic individuals. We discuss the implications of these findings for wellbeing, marketing, and sustainability.